Zeolite Effect on Solid Product Characteristics in Hydrothermal Treatment of Household Waste - Lalak Tarbiyatun Nasyin Maleiva; Chandra Wahyu Purnomo; Putranty Widha Nugraheni; Eka Kusumawardhani; Leonardus Sandy Ade Putra (Department of Chemical Engineering, Universitas Gadjah Mada, 2023)
The number of primary energy sources in Indonesia will run out quickly. Therefore, innovation is required to provide renewable energy sources (NRE) that accommodate the increasing energy necessities. Hydrothermal is the potential degradation process of plastic waste to generate NRE. This study aims to examine the effectiveness of the hydrothermal process in breaking down bulky raw materials and the role of zeolite as a catalyst to upgrade the quality of hydrochar as a novel solid fuel by evaluating the essential parameters through proximate and ultimate analysis. The addition of zeolite in the hydrothermal process can increase the water content, ash content, and volatile matter and slightly decrease the calorific value and fixed carbon. The condition to obtain the best characteristics was temperature of 220 oC and the addition of 20 % zeolite.